Seed Pre-Treatment and Planting Geometry Positively Influence Herbicide Efficacy in Wheat (Triticum aestivum) - ULLAH,A. (2018)
ABSTRACT: An experiment was conducted to evaluate the effect of priming, planting patterns and weed control treatments on weed spectrum, grain yield and profitability of wheat, during the growing season 2013-14. Two levels of seed priming (no priming, osmopriming) and planting patterns (broadcast, row plantation), and four levels of herbicide (pyroxulam at the rate of 14.08, 10.56, 7.04 and 7.521 g a.i. ha-1) were employed in the experiment, laid out in a randomized complete block design with split-split plot arrangement. The data regarding weed density, stand establishment, growth, and yield associated traits of wheat were recorded and analyzed by analysis of variance technique using statistical software DSAASTAT. The results revealed that the final emergence count was improved significantly by line sowing. The seed priming treatments resulted in early crop emergence and canopy spread, and it also decreased weed density and dry weight by 13% and 18%, respectively at 60 DAS (days after sowing). Moreover, grain yield was improved by 8% in priming treatment plots. Whereas, line sowing of wheat treatment decreased the weed density and dry weight by 17% and 25% respectively, with improved grain yield by 14% over the broadcast method. Pyroxulam at the rate of 14.08 g a.i. ha-1 applied at 60 DAS reduced total weed density and dry weight by 88% and 96% respectively and grain yield was improved by 36% over weedy check plots. In conclusion, osmoprimed seeds (1% KCl) sown in lines 22.5 cm apart gave higher wheat yields where weeds were properly controlled through application of pyroxulam applied at its recommended dose (14.08 g a.i. ha-1) and also 75% of recommended dose under Faisalabad conditions.